2007
DOI: 10.1097/01.prs.0000244745.21562.58
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Breast Reconstruction in the Diabetic Patient

Abstract: The present data indicate that type 1 diabetes mellitus and type 2 diabetes mellitus are not relative or absolute contraindications to microvascular TRAM flap breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 28 publications
0
22
2
1
Order By: Relevance
“…Additionally, several studies of other flap procedures have found that diabetes is not associated with a significantly increased wound complication rate. 27,28 Regarding malnutrition, the albumin and prealbumin levels we selected as the definition of malnutrition, 3.5 mg/dL and 18 mg/dL, respectively, may not accurately identify the level of malnourishment necessary to produce an adverse wound healing environment. These values were chosen because they represent the lower limit of normal on our institution's laboratory-reporting software.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies of other flap procedures have found that diabetes is not associated with a significantly increased wound complication rate. 27,28 Regarding malnutrition, the albumin and prealbumin levels we selected as the definition of malnutrition, 3.5 mg/dL and 18 mg/dL, respectively, may not accurately identify the level of malnourishment necessary to produce an adverse wound healing environment. These values were chosen because they represent the lower limit of normal on our institution's laboratory-reporting software.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Miller et al found no increase in free transverse rectus abdominis myocutaneous (TRAM) flap or donor-site complications between type 1 diabetic, type 2 diabetic, and nondiabetic patients (Level II Evidence) 38. Other studies examining diabetes and surgical complications have not achieved statistical significance (Level I/II Evidence) 24,29,39.…”
mentioning
confidence: 91%
“…Several studies have examined the relationship between several patient characteristics (other than adjuvant therapy) and complications (2,6,(42)(43)(44)(45), but there was variation in the factors studied, and inconclusive results.…”
Section: The Effect Of Patient Characteristics On Breast Reconstructionmentioning
confidence: 99%